The effects of instructor clarity and non-verbal immediacy on Chinese and Iranian EFL students’ affective learning: The mediating role of instructor understanding - Derakhshan, Ali; Zhang , Lawrence Jun; Zhaleh, Kiyana (Studies in Second Language Learning and Teaching, 2023)
Drawing on the rhetorical/relational goal theory, this study examined the role of instructor clarity and non-verbal immediacy in affective learning through the mediation of instructor understanding. Data were gathered through close-ended questionnaires from 756 Chinese and 715 Iranian English as a foreign language (EFL) students, the factor structure and cross-cultural validity of which were supported via confirmatory factor analysis and testing measurement invariance, respectively. Path analysis results indicated that clarity and non-verbal immediacy positively predicted instructor understanding and affective learning; instructor understanding positively predicted affective learning; and understanding was a significant positive mediator in the relationship of non-verbal immediacy and clarity with affective learning. Except for the positive association of non-verbal immediacy with understanding which was significantly higher for the Iranian group, no significant difference was found between the Chinese and Iranian groups in all other associations, providing empirical support for the role of EFL teachers’ positive interpersonal communication behaviors in EFL students’ affective learning, irrespective of the cultural context.